2013
DOI: 10.1038/ki.2012.424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intravascular volume status and volume responsiveness in critically ill patients

Abstract: Accurate assessment of a patient's volume status, as well as whether they will respond to a fluid challenge with an increase in cardiac output, is a critical task in the care of critically ill patients. Despite this, most decisions regarding fluid therapy are made either empirically or with limited and poor data. Given recent data highlighting the negative impact of either inadequate or overaggressive fluid therapy, understanding the tools and techniques available for accurate volume assessment is critical. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 133 publications
2
86
0
1
Order By: Relevance
“…However, intravascular volume status cannot be accurately evaluated on a clinical examination, and readily available point‐of‐care diagnostic tests such as arterial blood pressure and blood lactate concentration lack precision in estimating volume status. Central venous pressure (CVP) measurement historically has been used as an indirect measure of intravascular volume status . However, CVP measurement requires a central venous catheter, which is associated with a 39% complication rate including infection, thrombosis, and mechanical complications .…”
Section: Introductionmentioning
confidence: 99%
“…However, intravascular volume status cannot be accurately evaluated on a clinical examination, and readily available point‐of‐care diagnostic tests such as arterial blood pressure and blood lactate concentration lack precision in estimating volume status. Central venous pressure (CVP) measurement historically has been used as an indirect measure of intravascular volume status . However, CVP measurement requires a central venous catheter, which is associated with a 39% complication rate including infection, thrombosis, and mechanical complications .…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce the time required to recover from surgery, anesthesiologists and surgeons have developed hemodynamic protocols on the basis of the concept of goal-directed therapy (GDT). GDT protocols shift the perioperative physician's focus away from traditional hemodynamic end points (e.g., mean arterial pressure and central venous pressure, the latter of which is not at all predictive of the hemodynamic response to volume loading [164,165] and has been associated with impaired renal function in a variety of clinical environments) (166) and toward more modern end points: either cardiac output, stroke volume, and fluid responsiveness (the expected increase in cardiac index after a volume challenge) (164,165) or an index of oxygen supply to demand matching (e.g., SvO 2 ) (167).…”
Section: Prevention Of Aki Nonpharmacologic Strategiesmentioning
confidence: 99%
“…Static pressure measurements include CVP, pulmonary artery occlusion pressure, and echocardiography. Although CVP and pulmonary artery occlusion pressure have traditionally been used to guide fluid management, numerous studies have shown poor correlation of these parameters with predicting volume status, fluid responsiveness, and cardiac performance (42). Multiple factors affect the reliability of these parameters, including changes in venous tone, intrathoracic pressures (positive end expiratory pressure), left and right ventricular compliance, and IAP.…”
Section: Assessment Of Intravascular Volume In Critically Ill Patientsmentioning
confidence: 99%
“…Transesophageal echocardiography has been used to predict fluid responsiveness by assessing the left ventricular end diastolic area. However, interpretation is limited without baseline echocardiographic measurements for comparison (42).…”
Section: Assessment Of Intravascular Volume In Critically Ill Patientsmentioning
confidence: 99%